2005
DOI: 10.1111/j.1365-2494.2005.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon stocks in verges and urban areas of Flanders, Belgium

Abstract: Soil organic carbon (SOC) stocks in different terrestrial ecosystems have already been calculated. However, SOC stocks of grassy verges and grass-covered urban areas have never been reported. In this study the total grass-covered area of verges and urban areas in different agro-pedological regions of Flanders, Belgium was calculated and SOC stocks estimated. The total grassy area of verges along roads, waterways and railways was calculated to be 18 027 ha, 9530 ha for gardens and parks and 2360 ha for recreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(13 reference statements)
2
5
0
Order By: Relevance
“…Our results add to research illustrating the importance of natural capital from urban soils [8]. Small-scale urban green spaces can provide substantial carbon reserves: Mestdagh et al [79] found that SOC of "grassy roadsides, waterways and railways" in urban areas totaled 10%-15% of the toal SOC stocks in Flemish grasslands, though they do not report what percent of the urban area was covered by these small-scale urban green spaces (nor their relation to total urban SOC). Our results for SOC (38.4 ± 11.5 SD·kg·C·m −2 extrapolated to a 1-m depth) are comparable to other results for Chicago urban soils.…”
Section: Soil Carbon Stocksupporting
confidence: 54%
“…Our results add to research illustrating the importance of natural capital from urban soils [8]. Small-scale urban green spaces can provide substantial carbon reserves: Mestdagh et al [79] found that SOC of "grassy roadsides, waterways and railways" in urban areas totaled 10%-15% of the toal SOC stocks in Flemish grasslands, though they do not report what percent of the urban area was covered by these small-scale urban green spaces (nor their relation to total urban SOC). Our results for SOC (38.4 ± 11.5 SD·kg·C·m −2 extrapolated to a 1-m depth) are comparable to other results for Chicago urban soils.…”
Section: Soil Carbon Stocksupporting
confidence: 54%
“…In our results, the large variance in measured roadside width is reflected in the large standard deviation of the total roadside area. However, this large variance is confirmed by the large spread of the results of other studies [44][45][46]. Moreover, our results of productive area and biomass productivity are similar to the average of the values found by other authors for roadsides (125,000 ton FM [44] and 279,000 ton FM [46]).…”
Section: Biomass Potential Of Conservation Areas and Roadsides In Flasupporting
confidence: 95%
“…Different studies already tried to quantify the biomass production in roadsides and conservation areas in Flanders [44,45], but they had to rely on assumptions, rough estimations or semi-anecdotal data on biomass production and surface area. In our results, the large variance in measured roadside width is reflected in the large standard deviation of the total roadside area.…”
Section: Biomass Potential Of Conservation Areas and Roadsides In Flamentioning
confidence: 99%
“…Burning often leads to a large increase in carbon storage with increasing fine particulate soil organic carbon in grasslands (Bird et al 2000;Dai et al 2006). Some researchers reported frequent mowing management of turf grasslands enhances carbon storage in the soil (Qian and Follet 2002;Mestdagh et al 2005). Such grassland management practices may help to prevent succession from grassland to wasteland, as well as to enhance the amount of soil carbon and thus affect the regional carbon cycle.…”
Section: Introductionmentioning
confidence: 99%
“…2006). Some researchers reported frequent mowing management of turf grasslands enhances carbon storage in the soil (Qian and Follet 2002; Mestdagh et al. 2005).…”
Section: Introductionmentioning
confidence: 99%